An Analysis of Industry-Specific Variations and Sectoral Differences in Sustainability Disclosure among Indian Companies - Thassim, Shaima (Journal of Technology Management and Business, 2025)
The importance of understanding industry-specific variations and sectoral differences in sustainability disclosures is critical in today’s corporate landscape. Rapid urbanisation and industrialisation in India have created significant challenges for manufacturing companies, including environmental degradation, income inequality, and greenwashing. Balancing sustainability with economic growth remains a persistent issue, particularly in a developing economy like India. This study assesses the degree of industry-specific variations and sectoral differences in sustainability disclosures within the annual reports of 22 Indian manufacturing companies across various sectors. The study adopts a quantitative method and ex post facto research design, utilising data from the annual reports of sampled manufacturing companies for the fiscal years 2021–2022. The total enumeration sampling technique was employed, and data were validated through cross-examination of the annual reports by auditors. Content analysis was used to address key questions regarding document selection, environmental disclosure criteria, data processing, and scoring. Despite the increasing adoption of frameworks like the Global Reporting Initiative (GRI), International Integrated Reporting Council (IIRC), and Business Responsibility and Sustainability Reporting (BRSR-SEBI), greater knowledge and integration of these standards remain necessary. The findings highlight industry-specific trends, with some sectors demonstrating stronger commitments to sustainability reporting. The study concludes that Indian companies show a growing dedication to transparency and the adoption of sustainability frameworks, though sectoral differences persist. These findings underscore the need for standardized reporting practices and greater alignment with global sustainability goals to enhance corporate accountability and environmental stewardship.